2013
DOI: 10.1002/jor.22395
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐mediated interactions with extracellular matrix proteins for nucleus pulposus cells of the human intervertebral disc

Abstract: The extracellular matrix (ECM) of the human intervertebral disc is rich in molecules that interact with cells through integrin-mediated attachments. Porcine nucleus pulposus (NP) cells have been shown to interact with laminin (LM) isoforms LM-111 and LM-511 through select integrins that regulate biosynthesis and cell attachment. Since human NP cells lose many phenotypic characteristics with age, attachment and interaction with the ECM may be altered. Expression of LM-binding integrins was quantified for human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 28 publications
6
44
1
Order By: Relevance
“…These studies show that the ␤1 integrin, especially the ␣5␤1 heterodimer, is essential for NP cell attachment to fibronectin, collagen II, and lamin isoforms (LM-111 and LM-511), with additional contribution from ␣1, ␣2, and ␣3 integrin subunits (43)(44)(45). In the context of the disc degeneration, one study reported an increase in ␣5␤1 integrin expression in herniated disc tissue; it was speculated that the measured increase in fibronectin and collagen I was a result of altered cell-matrix interactions (46).…”
Section: Discussionmentioning
confidence: 86%
“…These studies show that the ␤1 integrin, especially the ␣5␤1 heterodimer, is essential for NP cell attachment to fibronectin, collagen II, and lamin isoforms (LM-111 and LM-511), with additional contribution from ␣1, ␣2, and ␣3 integrin subunits (43)(44)(45). In the context of the disc degeneration, one study reported an increase in ␣5␤1 integrin expression in herniated disc tissue; it was speculated that the measured increase in fibronectin and collagen I was a result of altered cell-matrix interactions (46).…”
Section: Discussionmentioning
confidence: 86%
“…Multiple cell surface receptors mediated the adhesion of laminins with chondrocytes and NP cells (Dürr et al, 1996;Gilchrist et al, 2007;Nettles et al, 2004), especially through integrins (Loeser, 2014). Blocking studies indicated that integrin β1 or α6β1 were primary receptors for strong cell attachment in human chondrocytes and NP cells (Bridgen et al, 2013;Dürr et al, 1996 …”
Section: The Effect Of Laminin On Chondrocyte Functionmentioning
confidence: 99%
“…Thus, scaffold modification to incorporate laminins could be applied to promote bioactivity of scaffolds in the 3D culture system (Brynda et al, 2009;Heydarkhan-Hagvall et al, 2012;Kang et al, 2012). He et al (2013) utilized laminin to modify poly(l-lactide) scaffolds and found that larger amounts of laminins could promote proliferation of mouse neonatal stem cells.…”
Section: Positive Effectsmentioning
confidence: 99%
“…An early decrease in their cell number, loss of this developmental phenotype, and infiltration of alternate cell types are considered critical events in the alterations in mechanical function associated with intervertebral disc degeneration [1-3]. NP cells may interact with collagens, fibronectin and laminins of the extracellular matrix (ECM) through integrin and non-integrin mediated mechanisms [4-10] with profound effects on cellular biosynthesis, attachment and morphology. Studies have shown the α5β1 integrin heterodimer regulates NP cell interactions with fibronectin [8], and are also involved in the onset of cell pathobiology following exposure to degraded fragments of fibronectin [11].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple isoforms of laminin are present in the juvenile NP, but not adjacent anulus fibrosus (AF) regions, as identified by immunohistochemical staining for the γ1 and other laminin chains [9, 12]. Porcine NP cells have been shown to interact with laminins LM-111 and LM-511 through integrins α6 and β1 [8, 13], while human NP cells derived from aged, degenerate tissues rely upon integrins α3, α5 and β1 for binding to these same laminins [10]. Together, these findings begin to reveal a role for specific integrin subunits in mediating NP cell-ECM interactions.…”
Section: Introductionmentioning
confidence: 99%